The revenge of Thomas Eakins - Kirkpatrick, Sidney D. (Henry McBride series in modernism and modernity., 2006)
Thomas Eakins was misunderstood in life, his brilliant work earned little acclaim, and hidden demons tortured and drove him. Yet, the portraits he painted more than a century ago captivate us today, and he is now widely acclaimed as the finest portrait painter our nation has ever produced. This book recounts the artist's life in fascinating detail, drawing on a treasure trove of Eakins' family correspondence and papers that have only recently been discovered. Never before has Thomas Eakins' story been told with such drama, clarity, and accuracy. Sidney Kirkpatrick sets the painter's life and art in the wider context of the changing world he devoted himself to portraying, and he also addresses the artist's private life - the contradictory impulses, obsessions, and possible psychological illness that fired his work. Kirkpatrick underscores Eakins's unflinching integrity as an artist and discloses how his profound appreciation of the beauty of the human form was both the source of his greatness and ultimately of his undoing. Nevertheless, the author observes, Eakins has had his 'revenge', inspiring a new generation of realist painters and gaining the recognition that eluded him in life.